2022
DOI: 10.3389/fcimb.2022.1044412
|View full text |Cite
|
Sign up to set email alerts
|

The filarial and the antibiotics: Single or combination therapy using antibiotics for filariasis

Abstract: Filarial infections caused by nematodes are one of the major neglected tropical diseases with public health concern. Although there is significant decrease in microfilariae (mf) prevalence following mass drug administration (IVM/DEC/ALB administration), this is transient, in that there is reported microfilaria repopulation 6-12 months after treatment. Wolbachia bacteria have been recommended as a novel target presenting antibiotic-based treatment for filarial disease. Potency of antibiotics against filarial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Since Wolbachia are Gram-negative bacteria, specific antibiotics have been used to eliminate the bacteria from their filarial host, leading to the eventual killing of the adult worms. Clinical trials with doxycycline have shown dramatic depletion (more than 99%) of Wolbachia from filarial nematodes (6-week treatment, 200 mg/day) that resulted in significant reduction of microfilaridermia and killing of O. volvulus adult worms [ 39 ] through the activation of apoptosis [ 40 ]. Importantly, treatment with such antibiotics is beneficial when people are co-infected with L. loa , a human filarial parasite that does not harbor an endosymbiont [ 39 ] but one, which, in high numbers, causes severe adverse events when individuals are treated with the drug ivermectin [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since Wolbachia are Gram-negative bacteria, specific antibiotics have been used to eliminate the bacteria from their filarial host, leading to the eventual killing of the adult worms. Clinical trials with doxycycline have shown dramatic depletion (more than 99%) of Wolbachia from filarial nematodes (6-week treatment, 200 mg/day) that resulted in significant reduction of microfilaridermia and killing of O. volvulus adult worms [ 39 ] through the activation of apoptosis [ 40 ]. Importantly, treatment with such antibiotics is beneficial when people are co-infected with L. loa , a human filarial parasite that does not harbor an endosymbiont [ 39 ] but one, which, in high numbers, causes severe adverse events when individuals are treated with the drug ivermectin [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wolbachia, an endosymbiotic bacterium of the order Rickettsiales, is present in arthropods. There is a symbiotic relationship between Wolbachia and filarial worms that is responsible for the filarial worms' development, embryogenesis, fertility and viability [13]. Tetracyclines (doxycycline and minocycline) are known to have an action against rickettsiae and therefore have been used against these novel targets.…”
Section: Discussionmentioning
confidence: 99%